<meta http-equiv="refresh" content="1; url=/nojavascript/"> Inverse of Functions through Algebraic Manipulation ( Read ) | Trigonometry | CK-12 Foundation
Dismiss
Skip Navigation
You are viewing an older version of this Concept. Go to the latest version.

Inverse of Functions through Algebraic Manipulation

%
Best Score
Practice Inverse of Functions through Algebraic Manipulation
Practice
Best Score
%
Practice Now
Inverse of Functions through Algebraic Manipulation
 0  0  0

If you were given a function, such as f(x) = \frac{2x}{x+7} , can you tell if the function has an inverse? Is there a way that you could find its inverse through algebraic manipulation?

Read on, and you'll find out how to do just that in this Concept.

Watch This

James Sousa: Inverse Functions

Guidance

An "inverse" is something that undoes a function, giving back the original argument. For example, a function such as y = \frac{1}{3}x has an inverse function of y = 3x , since any value placed into the first function will be returned as what it originally was if it is input into the second function. In this case, it is easy to see that to "undo" multiplication by \frac{1}{3} , you should multiply by 3. However, in many cases it may not be easy to infer by examination what the inverse of a function is.

To start, let's examine what is required for a function to have an inverse. It is important to remember that each function has an inverse relation and that this inverse relation is a function only if the original function is one-to-one. A function is one-to-one when its graph passes both the vertical and the horizontal line test. This means that every vertical and horizontal line will intersect the graph in exactly one place.

This is the graph of f(x) = \frac{x}{x+1} . The graph suggests that f is one-to-one because it passes both the vertical and the horizontal line tests. To find the inverse of f , switch the x and y and solve for y .

First, switch x and y .

x = \frac{y}{y+1}

Next, multiply both sides by (y + 1) .

(y+1)x & = \frac{y}{y+1} (y+1)\\x(y+1) & = y

Then, apply the distributive property and put all the y terms on one side so you can pull out the y .

xy+x & = y\\xy-y & = -x\\y(x-1) & = -x

Divide by (x - 1) to get y by itself.

y = \frac{-x}{x-1}

Finally, multiply the right side by \frac{-1}{-1} .

y = \frac{x}{1-x}

Therefore the inverse of f is f^{-1}(x)=\frac{x}{1-x} .

The symbol f^{-1} is read “ f inverse” and is not the reciprocal of f .

Example A

Find the inverse of f(x) = \frac{1}{x-5} algebraically.

Solution: To find the inverse algebraically, switch f(x) to y and then switch x and y .

y & =\frac{1}{x-5}\\x & = \frac{1}{y-5}\\x(y-5) & = 1\\xy-5x & = 1\\xy & = 5x+1\\y & = \frac{5x+1}{x}

Example B

Find the inverse of f(x) = 5 \sin^{-1} \left ( \frac{2}{x-3} \right )

Solution:

a. f(x) & = 5 \sin^{-1} \left ( \frac{2}{x-3} \right )\\x & = 5 \sin^{-1} \left ( \frac{2}{y-3} \right )\\\frac{x}{5} & = \sin^{-1} \left ( \frac{2}{y-3} \right )\\\sin  \frac{x}{5}  & = \left ( \frac{2}{y-3} \right )\\(y-3)\sin  \frac{x}{5}  & = 2\\(y-3) & = \frac{2}{\sin \frac{x}{5} }\\y & = \frac{2}{\sin \frac{x}{5} } + 3

Example C

Find the inverse of the trigonometric function f(x) = 4 \tan^{-1}(3x + 4)

Solution:

x & = 4\tan^{-1}(3y+4)\\\frac{x}{4} & = \tan^{-1}(3y+4)\\\tan  \frac{x}{4}  & = 3y+4\\\tan \frac{x}{4}  - 4 & = 3y\\\frac{\tan \frac{x}{4} -4}{3} & = y\\f^{-1} (x) & = \frac{\tan  \frac{x}{4} -4}{3}

Vocabulary

Horizontal Line Test: The horizontal line test is a test applied to a function to see how many times the graph of a function intersects an arbitrary horizontal line drawn across the coordinate grid. A function passes this test if it intersects the horizontal line in only one place, no matter where the horizontal line is drawn.

One to One Function: A one to one function is a function that passes both the horizontal and vertical line tests.

Vertical Line Test: The vertical line test is a test applied to a function to see how many times the graph of a function intersects an arbitrary vertical line drawn across the coordinate grid. A function passes this test if it intersects the vertical line in only one place, no matter where the vertical line is drawn.

Guided Practice

1. Find the inverse of f(x) = 2x^3-5

2. Find the inverse of y = \frac{1}{3}\tan^{-1} \left ( \frac{3}{4}x-5 \right )

3. Find the inverse of g(x)=2\sin (x-1)+4

Solutions:

1.

f(x) & = 2x^3-5\\y & = 2x^3-5\\x & = 2y^3-5\\x + 5 & = 2y^3\\\frac{x+5}{2} & = y^3\\\sqrt[3]{\frac{x+5}{2}} & = y

2.

y & = \frac{1}{3} \tan^{-1}\left ( \frac{3}{4}x-5 \right )\\x & = \frac{1}{3}\tan^{-1}\left ( \frac{3}{4}y-5 \right )\\3x & = \tan^{-1}\left ( \frac{3}{4}y-5 \right )\\\tan (3x) & = \frac{3}{4}y-5\\\tan (3x) + 5 & = \frac{3}{4}y\\\frac{4(\tan (3x)+5)}{3} & = y

3.

g(x) & = 2 \sin (x-1)+4\\y & = 2 \sin (x-1)+4\\x & = 2 \sin (y-1)+4\\x-4 & = 2 \sin (y-1)\\\frac{x-4}{2} & = \sin (y-1)\\\sin^{-1} \left ( \frac{x-4}{2} \right ) & = y-1\\1 + \sin^{-1} \left ( \frac{x-4}{2} \right ) & = y

Concept Problem Solution

Since the original function is:

f(x) = y = \frac{2x}{x+7}

You can first switch all of the "x" and "y" values:

x = \frac{2y}{y+7}

You can then rearrange the equation and isolate "y":

x(y+7) = 2y\\xy + 7x = 2y\\xy - 2y = -7x\\y(x - 2) = -7x\\y = \frac{-7x}{x - 2}\\

The inverse function is written as f^{-1}(x) = \frac{-7x}{x - 2}

Practice

Find the inverse of each function.

  1. f(x)=3x+5
  2. g(x)=0.2x-7
  3. h(x)=0.1x^2
  4. k(x)=5x+6
  5. f(x)=\sqrt{x-4}
  6. g(x)=(x)^{\frac{1}{3}}+1
  7. h(x)=(x+1)^3
  8. k(x)=\frac{x^2}{3}
  9. f(x)=-2+4 \sin^{-1}(x + 7)
  10. g(x)=1+3 \tan^{-1}(2x + 1)
  11. h(x)=4 \cos^{-1}(3x)
  12. k(x)=-1 \tan^{-1}(6x)
  13. j(x)=5+2 \sin^{-1}(x + 5)
  14. m(x)=-2 \tan(3x + 1)
  15. p(x)=5-6 \sin(\frac{x}{2})

Image Attributions

Reviews

Email Verified
Well done! You've successfully verified the email address .
OK
Please wait...
Please wait...

Original text